Improving Deaf Students’ Interest in Learning English through 3D Animation Media - Syamsiarna Nappu; Maemuna Muhayyang; Amsar Ramadhan; Aliyah Nur Khalizah; Hazah Agung Izni (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates whether 3D animation media increase deaf students’ interest in learning English at SLB Negeri 1 Makassar. The study was motivated by the persistent difficulty of delivering English input to deaf learners through conventional verbal explanation and static print materials. Because deaf students depend strongly on visual access, learning media that combine movement, imagery, contextualized vocabulary, and sign-supported explanation are expected to attract attention and sustain engagement more effectively. The study employed a pre-experimental group design. Ten eleventh-grade deaf students participated in the study. Data were collected through a Likert-scale questionnaire administered before and after the treatment. The treatment consisted of English lessons supported by 3D animated videos and animated films, accompanied by guided questioning and sign language practice. Data were analyzed using descriptive statistics. The findings indicate a meaningful increase in students’ interest in learning after the intervention. The mean score rose from 87.40 before the treatment to 103.30 after the treatment, while the significance value of 0.018 showed a statistically significant difference between the two measurements. The score distribution also shifted from neutral responses toward interested and strongly interested categories. These findings suggest that 3D animation media can make English instruction more visually accessible, engaging, and motivating for deaf learners. The study contributes practical evidence that visually rich media can support inclusive English pedagogy in special-school contexts and may serve as an alternative instructional resource for teachers working with deaf students.